Natural multi-target modulators of pathological pathways in Alzheimer's disease isolated from the Rhinella arenarum skin. Issue 12 (15th June 2022) - Spinelli, Roque; Rietmann, Álvaro; Sanchis, Ivan; Siano, Álvaro Sebastián
Abstract: The skin of anuran amphibians is a rich source of compounds with great medicinal potential. Alzheimer's disease (AD) is a complex disease associated with numerous pathological pathways, making their simultaneous modulation necessary. Nowadays the development of anti-AD drugs is focused on a Multi-Target Directed Ligands strategy. Herein we report the bioactivity of the skin extracts of the toad Rhinella arenarum obtained by an invasive and non-invasive methods, against five AD pathological targets (AChE, BChE, MAO-B, antioxidant and chelating activities). The extract derived from the non-invasive technique showed the highest biological activity, being capable of acting on all or almost all the pathological targets of AD, while also avoiding harm to the animal. Graphical abstract: UF0001